The exchange rate and monetary conditions in the euro area - David G. Mayes; Matti Virén (Bank of Finland, 1998)
Using information from a variety of sources, including our own estimates from quarterly data for each of the countries over the period 1972-1997, this paper suggests that the exchange rate will play an important role in the transmission of the impact of monetary policy through to the real economy and inflation in the euro area.Although the share of external trade in the euro area's GDP is only around 10 per cent this is only one factor that affects the transmission mechanism and the role of the exchange rate is likely to be substantially greater when all factors are taken into account.As a first approximation it would be reasonable to assume that an increase in the real 90-day interest rate of 100 basis points would have approximately the same effect on demand pressure two years later as a 3.5 per cent fall in the real euro exchange rate.This implies that the euro area will tend to behave like a large open economy rather than a closed economy and hence that it would be helpful in informing monetary policy to construct a Monetary Conditions Index (MCI) using these weights.A separate paper (Mayes and Virén 1998) suggests how an MCI provides a useful summary of high frequency information to assist monetary policy and financial markets in short run decisions..
URN:NBN:fi:bof-20140807282
Keywords: 330; monetary conditions index; exchange rate; monetary policy; euro area